Valuing the Firm's Durable Assets for Managerial Information. - Goldschmidt, Y.; Smidt, S. (The Accounting Review, 1969)
This article discusses a plausible method of valuing individual durable assets, not valuing those of the whole firm, for internal, managerial purposes; that is, for decisions and control. In this paper a method of valuation is explored that is appropriate for an accounting system when its primary purpose is to provide data for managerial decision-making. Three basic approaches to the valuation of individual assets are available. They are: the first one is past transactions, second is future earning power, and the third one is present market price. These approaches can be stated in terms of the costs which are used as a basis for valuing the assets. They are original cost, internal opportunity cost, and external opportunity cost. External opportunity cost is defined as a market price of an asset that is to be used in production rather than bought or sold. Internal opportunity cost is the present value of the incremental cash flow an asset or a set of assets can earn in its feasible use within the firm.